Prevalence of alcohol use disorder among the Latvian general population and associations with the PHQ-9 screening results and sociodemographic factors - V.V. Vinogradova; A. Kivite-Urtane; J. Vrublevska; E. Rancans (European Psychiatry, 2022)
Introduction Both alcohol use disorder (AUD) and depression are potentially disabling and economically burdensome disorders. There is no available information about the prevalence of alcohol use disorder in the general population of Latvia.